Efektivitas Strategi Penerapan Zakat Sebagai Pengurang Pajak Penghasilan Pada Lembaga Amil Zakat - Jinan, Ulfatul; Makhtum, Ahmad (Forum Kerjasama Pendidikan Tinggi, 2024)
The purpose of this research is to find out the strategies implemented by the Nurul Hayat Surabaya zakat institution in implementing the zakat policy as a deduction from income tax. The method used in this research is descriptive qualitative. The data used in this research is primary data and also secondary data. The use of primary data in this research was obtained from documentation, observation and also interviews. Meanwhile, the secondary data used in this research comes from literature studies such as books, journals and report documents that are available and in accordance with the title of this research. To achieve the predetermined targets, the Nurul Hayat Surabaya amil zakat institution uses a promotional strategy on social media, of course this attracts the interest of the public who see promotional content belonging to the Nurul Hayat amil zakat institution to pay their zakat at the Nurul Hayat amil zakat institution, hence the strategy This is quite effective because the scope or scope for being seen by the public is quite wide.